2020
DOI: 10.1002/fes3.266
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on household food security and adaptation strategies in southern Ethiopia

Abstract: Climate change is predicted to adversely affect agricultural yields, particularly in African countries such as Ethiopia, where crop production relies heavily on environmental factors such as rainfall and temperature. However, there have only been a limited number of studies on the effects of climate change dynamics on food security in Africa, particularly at the household level. We therefore analyzed local climatic changes, the status of household food security, climate‐related causes of food insecurity, food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Kuwornu et al [31] and Frimpong [32] in Ghana found 78.5% and 60% of the households respectively food insecure, which falls to meet the minimum calorie requirement. Mesfin [27], Weldearegay and Tedla [15] and Mekonnen et al [16] observed in their studies of the impact of climate variability on household food in Ethiopia that 56.0%, 84.3% and 60.5% of the households respectively were food insecure fell below the daily recommended calorie intake.…”
Section: Food Security Status Of the Farm Householdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuwornu et al [31] and Frimpong [32] in Ghana found 78.5% and 60% of the households respectively food insecure, which falls to meet the minimum calorie requirement. Mesfin [27], Weldearegay and Tedla [15] and Mekonnen et al [16] observed in their studies of the impact of climate variability on household food in Ethiopia that 56.0%, 84.3% and 60.5% of the households respectively were food insecure fell below the daily recommended calorie intake.…”
Section: Food Security Status Of the Farm Householdsmentioning
confidence: 99%
“…Globally, climate variability coupled with wars, natural disasters and political instability are mentioned to be direct cause of food insecurity for millions of people in the world [13]. Previous studies have shown that changes in climatic condition largely affect food productions system and food security [14][15][16]. Wheeler and Von Braun [17] pointed out that climate variability is the main driver of food security in the developing world, because it affects the productivity of the agriculture, its stability and food systems.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have attempted to assess farmers’ awareness of climate change/variability and its impacts on agriculture in Ethiopia ( Belay et al., 2017 ; Below et al., 2015 ; Etana et al., 2021 ; Mekonnen et al., 2021 ; Mekuyie and Mulu, 2021 ; Thinda et al., 2021 ; Zerssa et al., 2021 ). On the one hand, it has been reported that most farmers have noticed a change in climate ( Weldegebriel and Prowse, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Drought arises from a negative balance of water supply and demand and can be categorised in terms of intensity, duration, and extent (Funk & Shukla, 2020). Ethiopia has experienced multiple drought events over recent decades and is particularly exposed to climate‐related impacts due to its dependence on rain‐fed subsistence agriculture (Cochrane, 2017; Mekonnen et al, 2020). Extreme drought and famine in 1983–1984 resulted in over one million deaths from starvation and malnutrition (Fazzini et al, 2015) and more recent severe droughts occurred in 2000, 2002–2003, 2009, 2011, and 2015 (Bewket & Conway, 2007; Cochrane, 2017; Mera, 2018; Viste et al, 2013).…”
Section: Introductionmentioning
confidence: 99%